Didactic strategy for the interdisciplinary formation of the Physical culture graduate - Jacinto Enrique Mendoza-Díaz (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2015)
In the Physical Culture and Sports sciences University of Santiago de Cuba are developed different scientific research projects, one of them is named Professional's Formati on, in which are registered the results of the research that is proposing. The investigative task that is the study object is conceived a didactic methodological strategy that promote a teaching learning process from a holistic approach of knowledge, skill s, values, methodologies and ways of thinking that point to interdisciplinary. In essence, the present work proposes a didactic strategy for the interdisciplinary formation of the Physical Culture graduate; it has as objective to develop the interdisciplin ary formation that favors a coherent performance in the academic, working and investigative activities they do. The didactic strategy presents necessary important aspects for the teachers and students in its structural conception, it is structured in three stages with a system of actions that in the educative practice lead to the Physical Culture graduate interdisciplinary formation.